The Suitability Level of Ecotourism Characteristics in the Sipin Lake Tourist Destination in Jambi City - Simamora, Rio Gabriel; Yuliastuti, Nany (E-Journal of Tourism; Volume 10 Number 2 (September 2023)DO - 10.24922/eot.v10i2.108625, 2023)
The activity of tourism has more potential to be a new income source in an area with tourism destination. The united nations world tourism organization (UNWTO) released the number of world tourism activities in 2018, which reached 1.4 billion. Global development, including tourism development, is guided by the SDGs. The form of increasingly dynamic tourism activities cannot be separated from the existence of attractions, amenities, accessibility, and institutional services. Jambi City has the tourism object of Sipin Lake as a potential tourism destination that has yet to be developed maximally to have high competitiveness. The research aims to assess the suitability level of ecotourism aspects at the Sipin Lake tourist destination. The analysis method used is a quantitative method using the Importance-Performance Analysis (IPA) method. The average result of the level of suitability of all variables of the characteristics of ecotourism is 60%, where attractions (61%), accessibility (101%), amenities (61%), institiutional services (42%), and environmental conservation (34%).